(untitled) (Élisée - Revista de Geografia da UEG, 2020)
To understand the agrarian issue today we consider it necessary to use certain concepts and analytical categories. In this regard, we problematize the reproduction of the concept of neoextractivism proposed by Eduardo Gudynas in Brazilian Geography. Neo-extractivism promotes deep territorial impacts, hence the need for a study that aims to contemplate the materiality of its reproduction, aiming at its geographical operationalization. For this, the methodology carried out relied on empirical research carried out in Mozambique in comparison with theses and geographical dissertations that make use of the concept in question, relating it to geographical analytical categories. The study presented here resulted in the confirmation of conceptual reproduction and an approximation of its operationalization in the field of research in Geography. Keywords: Geography. Neoextractivism. Agrarian question. Operationalization